Along-Strike Rapid Structural and Geomorphic Transition From Transpression to Strike-Slip to Transtension Related to Active Microplate Rotation, Papua New Guinea - Sun, Lei; Mann, Paul (Frontiers in Earth Science, 2021)
The area of southeastern Papua New Guinea includes three active microplates - the Trobriand, Woodlark, and Solomon Sea plates – that are being deformed by regional convergence between the much larger Pacific and Australian Plates. The landward extent of the plate boundary between the Trobriand and Australian Plates corresponds to the Owen-Stanley Fault Zone (OSFZ), a 510 km-long left-lateral strike-slip fault that forms a linear, intermontane valley within the elongate Owen-Stanley Range (OSR) and extends into a 250 km-long low angle normal fault along the margins of Goodenough and Woodlark basins. Modern GPS geodesy reveals that the Trobriand microplate has undergone rapid counter-clockwise rotation since the Late Miocene (8.4 Ma) and that this rotation about a nearby pole of rotation predicts transpressional deformation along the 250 km-long northwestern segment of the OSFZ, strike-slip motion along a 100 km-long central segment, and transtension along the 270 km-long ESE-trending southeastern segment of OSFZ. In order to illustrate the along-strike variations in neotectonic uplift resulting from the changing structure of the OSFZ, we delineated a river network of 3903 river segments in the northeastern side of OSR drainage divide and derived river longitudinal profiles along each river segment. Normalized steepness indices (ksn) and knickpoint clusters are highest and most concentrated, respectively, for the northwestern transpressional segment of the OSR, moderately high and concentrated along the southeastern segment of the OSR, and lowest and least concentrated along the central strike-slip segment extending southeast into transtension. These geomorphological indices indicate the most areas of plate boundary uplift occur along the transpressional and transtensional segments that are connected by the central strike-slip zone that is characterized by less vertical fault movements. Within this overall pattern of structural variation, abrupt changes in the azimuth of the OSFZ create more localized anomalies in the geomorphological indices.